Operations Research in Solving a Marketing Problem - Cross, James S. (Journal of Marketing, 1961)
An Operations Research task group was assembled at the Sun Oil Company to consider future product policies. Possible courses of action were: (1) To retain the policy of marketing only a single grade of gasoline. (2) To market a regular and a premium grade, similar to competition. (3) To market three grades of gasoline: regular, premium, and super-premium. (4) To continue the “Blue Sunoco” grade, but with an “octane concentrate” which could be custom blended at the pump to produce a wide range of fuels. This article explains how the group provided management with the data necessary to make the decision.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDIyMjQyOTYxMDI1MDAzMDY